ACTH-Independent Cushing's Syndrome Associated with Left Adrenocortical Oncocytoma of Uncertain Malignant Potential. (27th September 2020) - Sica, Giuseppe S.; Siragusa, Leandro; Sensi, Bruno; Bellato, Vittoria; Floris, Pierangela; Rovella, Valentina; Mauriello, Alessandro; Di Prete, Monia; Telesca, Rossana; Ciavoni, Valerio; Cardillo, Carmine; Di Daniele, Nicola; et al.
Abstract : Adrenocortical oncocytomas are rare and mostly nonfunctioning neoplasms. We report the case of a 27-year-old woman diagnosed with an ACTH-independent Cushing's syndrome due to left adrenal oncocytoma. She underwent laparoscopic adrenalectomy. Histopathological examination revealed an oncocytoma of uncertain malignant potential with a low Ki-67 proliferation index, inhibin A positivity, and chromogranin A negativity. Electron micrographs confirmed adrenal oncocytoma cells, characterized by the presence of a large amount of mitochondria. The postoperative course was uneventful, and the patient experienced a progressive regression of Cushing-related symptoms. Periodical follow-ups with MRI and cortisol dosage are required due to the neoplasm's uncertain malignant potential. Considerations on the diagnosis, pathology findings, clinical remarks, and interventions are made.